2016
DOI: 10.1016/j.watres.2016.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction, phytotransformation and rhizodegradation of ibuprofen associated with Typha angustifolia in a horizontal subsurface flow constructed wetland

Abstract: a b s t r a c tWidespread occurrence of trace pharmaceutical residues in aquatic environments is of great concerns due to the potential chronic toxicity of certain pharmaceuticals including ibuprofen on aquatic organisms even at environmental levels. In this study, the phytoextraction, phytotransformation and rhizodegradation of ibuprofen associated with Typha angustifolia were investigated in a horizontal subsurface flow constructed wetland system. The experimental wetland system consisted of a planted bed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 44 publications
(57 reference statements)
0
6
2
2
Order By: Relevance
“…Matamoros et al [20,64]; Hijosa-Valsero et al [15,65]; Ávila et al [23,35,38,59,61]; Matamoros and Salvadó [14]; Li et al [8]; Zhu and Chen [66]; Chen et al [17]; Vymazal et al [19]; Březinova et al [67]; Zhang et al [34]; Nivala et al [43] Biodegradation (aerobic) Sorption Dordio et al [44]; Dordio and Carvalho [28] Adsorption Auvinen et al [31] Photodegradation Reyes-Contreras et al [48]; Zhang et al [10] Plant uptake Hijosa-Valsero et al [15]; Li et al [51] Ketoprofen Biodegradation Hijosa-Valsero et al [15]; Zhang et al [27]; Chen et al [17]; Francini et al [62]; Zhang et al [34] Photodegradation…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matamoros et al [20,64]; Hijosa-Valsero et al [15,65]; Ávila et al [23,35,38,59,61]; Matamoros and Salvadó [14]; Li et al [8]; Zhu and Chen [66]; Chen et al [17]; Vymazal et al [19]; Březinova et al [67]; Zhang et al [34]; Nivala et al [43] Biodegradation (aerobic) Sorption Dordio et al [44]; Dordio and Carvalho [28] Adsorption Auvinen et al [31] Photodegradation Reyes-Contreras et al [48]; Zhang et al [10] Plant uptake Hijosa-Valsero et al [15]; Li et al [51] Ketoprofen Biodegradation Hijosa-Valsero et al [15]; Zhang et al [27]; Chen et al [17]; Francini et al [62]; Zhang et al [34] Photodegradation…”
Section: Methodsmentioning
confidence: 99%
“…For instance, root uptake of ibuprofen was partially transformed to carboxyibuprofen, 2-hydroxyibuprofen, and 1-hydroxyibuprofen in the sheath (1375, 236, and 302 ng•g −1 , respectively) and in the lamina (1051, 694, and 179 ng•g −1 , respectively). The accumulation of transformation products (TPs) of ibuprofen in the leaves of Typha angustifolia is evidence of the phytotransformation of ibuprofen in plant tissues [51]. In addition to that, He et al [52] noted the phytotransformation of TPs of ibuprofen.…”
Section: Role Of Plantsmentioning
confidence: 99%
“…In the aqueous phase in the light compartment of CW2, occurrence of hydroxy-IBP was also observed resulting from photodegradation. Dihydroxy-IBP and carboxy-IBP were found in biodegradation studies of IBP [124,226], but were not observed in our studies reported here.…”
Section: Ibp Intermediates In Mesocosm Cwscontrasting
confidence: 86%
“…All seven tested PhACs were found to accumulate in both RR and SL tissues (Table 8.1). To date, there are studies in which plant uptake of CAF, NAP, IBP, DFC, and CBZ in wetland plant species was detected [104,158,226,396,398,399]; our data showing β-blocker uptake (i.e. MET and PRO) has not been reported previously.…”
Section: Phac Abundance In Plantscontrasting
confidence: 66%
See 1 more Smart Citation